2015
DOI: 10.1063/1.4906361
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional hybrid Monte Carlo–fluid modelling of dc glow discharges: Comparison with fluid models, reliability, and accuracy

Abstract: Two-dimensional hybrid Monte Carlo-fluid numerical code is developed and applied to model the dc glow discharge. The model is based on the separation of electrons into two parts: the low energetic (slow) and high energetic (fast) electron groups. Ions and slow electrons are described within the fluid model using the drift-diffusion approximation for particle fluxes. Fast electrons, represented by suitable number of super particles emitted from the cathode, are responsible for ionization processes in the discha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 28 publications
0
10
0
2
Order By: Relevance
“…In this case, electron heating source in the plasma becomes nonlocal, because the effect of heating caused by the heat flux from the cathode layer, where main Joule heating occurs, is taken into account properly. Analysis of the calculation results showed [15]- [24] that the model describes adequately basic properties of glow discharge, reproduces correctly currentvoltage characteristics (CVCs), and specific discharge modes occurring along the CVC (including normal mode and formation of a normal current density in 2-D simulations) as well as 2-D spatial profiles of such discharge parameters as charged particle densities, electron temperature, electric potential, and electric field.…”
Section: A System Of Equationsmentioning
confidence: 87%
See 1 more Smart Citation
“…In this case, electron heating source in the plasma becomes nonlocal, because the effect of heating caused by the heat flux from the cathode layer, where main Joule heating occurs, is taken into account properly. Analysis of the calculation results showed [15]- [24] that the model describes adequately basic properties of glow discharge, reproduces correctly currentvoltage characteristics (CVCs), and specific discharge modes occurring along the CVC (including normal mode and formation of a normal current density in 2-D simulations) as well as 2-D spatial profiles of such discharge parameters as charged particle densities, electron temperature, electric potential, and electric field.…”
Section: A System Of Equationsmentioning
confidence: 87%
“…Analysis of different simulation approaches, conducted in [15], indicated that extended fluid model is the most developed and established model and that it was successfully tested on various gas discharges. This model was proposed in [16] and [17] and developed in [18]- [24].…”
Section: Introductionmentioning
confidence: 99%
“…Для моделирования движения электронов в настоящей работе применяется методи-ка, основанная на использовании метода Монте-Кар-ло [20][21][22]. Учитывается упругое рассеяние электронов на атомах компонент смеси, а также возбуждение и ионизация ими невозбужденных и метастабильных ато-мов с использованием зависимостей сечений этих про-цессов от скорости электрона, приведенных в [23][24][25].…”
Section: описание модели разрядаunclassified
“…In [31], a thorough analysis of existing simulation approaches for gas discharge simulation was performed. It was indicated that extended fluid model developed in [32] and [33] is the most consistent model and that it has been successfully tested on various gas discharges [34]- [36], [40].…”
Section: Introductionmentioning
confidence: 99%